Hydrological characterization of the micro-watershed of the Hondo stream, canton of La Maná, Ecuador - Macas Cobeña, Marilyn (2023)
The objective of this research is to characterize the hydrological network of the “Hondo” estuary micro-basin through the use of morphometric and biophysical parameters, in order to analyze and predict its hydrodynamic behavior, in order to contribute to environmental management plans and be a contribution to the conservation and protection of optimal conditions for their development. Three shape parameters, two of relief, its drainage network and physiography were analyzed. While in the biophysical variables they were calculated by means of ArcGIS geospatial information processing, identifying their temperature, precipitation, soil texture, land use and cover, slope and taxonomy. According to the results obtained, its morphometry the micro-basin presented an oblong or rectangular shape, a moderate drainage network, where it is concluded that its water system is not prone to present flood peaks, due to the stability of its runoff regimes. superficial. However, as it is a young basin and presents a concave hypsometric shape, it is likely that it will experience high erosive processes in the future. Finally, in the biophysical component it was identified that the texture of the soil was mostly sandy loam, with strong and steep slopes and a predominance of alfisols whose water filtration is low, where it is concluded that the micro-basin could present loss of the layer vegetative by dragging sediment.